UWARUNKOWANIA I KIERUNKI ZMIAN W PROCESACH DECYDOWANIA PUBLICZNEGO NA SZCZEBLU SAMORZĄDOWYM W ZWIĄZKU Z PANDEMIĄ KORONAWIRUSA - Mroczka, Kamil (Polityka i Społeczeństwo, 2021)
In recent months, the COVID-19 virus has become a key challenge for all countries, regardless of their geographical location, economic situation or system of government. As stated by Grzegorz Rydlewski, the crisis has become a condition for balancing and targeting the activities of supranational structures, states, various intermediate structures, and individual people (Rydlewski, 2020). The main aim of the present article is to discuss the trends and changes to public decision-making processes introduced by the lawmaker in connection with the epidemic threat to local government administration. Unquestionably, one of the negative effects of the pandemic is the fact that holding meetings of local government bodies in physical form has been unsafe since the outbreak. Legal and technical solutions have been introduced which partly transfer the decision-making process to the digital world by allowing remote meetings for a wide range of statutory bodies. In this context, it is important to examine the usefulness, practicality and efficiency of the solutions adopted, and also to identify key obstacles and challenges to local government decision-making processes. Additionally, examples of ICT tools supporting decision making in local government units will be duly provided. Finally, key problems identified in the course of the analysis in question, e.g., issues related to the area of cyber security, will be also highlighted.